Teaching patient-centred communication skills during clinical procedural skill training: a preliminary pre-post study comparing international and local medical students - Nagy, Ede; Luta, Gloria; Huhn, Daniel; Cranz, Anna; Schultz, Jobst-Hendrik; Herrmann-Werner, Anne; Bugaj, Till Johannes; Friederich, Hans-Christoph; Nikendei, Christoph (BMC medical education, 2021)
Background: International medical students are frequently confronted with intercultural, psychosocial, and language barriers and often receive lower marks in written, oral, and clinical-practical examinations than fellow local students. Training communication competence in procedural skills, such as blood sampling, is further challenge in this particular group of medical students. This pre-post comparative intervention study aimed to investigate the effects of training communication skills during the performance of procedural skills (taking blood samples from a silicone model) in international and local students as part of their clinical practical medical training. Methods: Study participants performed blood sampling on an arm prosthesis model (part-task trainer) before and after the communication skills training, focusing on accompanying communication with a simulation patient sitting next to the arm model. The pre- and post-evaluation video was assessed by two independent evaluators using a binary checklist, the Integrated Procedural Performance Instrument (IPPI) and global assessments of clinical professionalism in terms of procedural and communication performance. Linear models with mixed effects were used. Group differences regarding global competence levels were analysed with χ2-tests. Results: International medical students did not perform as well as their local counterparts in the pre- and post-examinations. Both groups improved their performance significantly, whereby the international students improved more than their local counterparts in terms of their communication performance, assessed via binary checklist. Clinical professionalism evaluated via global assessments of procedural and communication performance highlights the intervention’s impact insofar as no international student was assessed as clinically not competent after the training. Conclusions: Our results suggest that already a low-dose intervention can lead to improved communication skills in medical students performing procedural tasks and significantly increase their confidence in patient interaction.
Gesehen am 19.10.2021